2021
DOI: 10.3390/vaccines10010039
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Obtaining COVID-19 Vaccination among Health Care Workers with Access to Free COVID-19 Vaccination: A Cross-Sectional Study

Abstract: Introduction: Despite global efforts to contain the illness, COVID-19 continues to have severe health, life, and economic repercussions; thus, maintaining vaccine development is mandatory. Different directions concerning COVID-19 vaccines have emerged as a result of the vaccine’s unpredictability. Aims: To study the determinants of the attitudes of healthcare workers (HCWs) to receiving or refusing to receive the vaccine. Methods: The current study adopted an interviewed questionnaire between June and August 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 48 publications
(67 reference statements)
0
23
0
Order By: Relevance
“…HCWs of over 60 years of age were the most likely to accept a COVID-19 vaccine compared to other age groups in studies from the UK, Germany, Switzerland, and Azerbaijan [ 10 , 17 , 43 , 63 ]. Contrastingly, five articles from Italy, China, Egypt, and Palestine found that younger HCWs (18–<30) are more likely to accept COVID-19 vaccines [ 14 , 15 , 18 , 31 , 37 ]. Interestingly, the aforementioned Egyptian study reports higher acceptance among younger HCWs; however, it was not a predictor for COVID-19 vaccination [ 18 ].…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…HCWs of over 60 years of age were the most likely to accept a COVID-19 vaccine compared to other age groups in studies from the UK, Germany, Switzerland, and Azerbaijan [ 10 , 17 , 43 , 63 ]. Contrastingly, five articles from Italy, China, Egypt, and Palestine found that younger HCWs (18–<30) are more likely to accept COVID-19 vaccines [ 14 , 15 , 18 , 31 , 37 ]. Interestingly, the aforementioned Egyptian study reports higher acceptance among younger HCWs; however, it was not a predictor for COVID-19 vaccination [ 18 ].…”
Section: Resultsmentioning
confidence: 98%
“…Contrastingly, five articles from Italy, China, Egypt, and Palestine found that younger HCWs (18–<30) are more likely to accept COVID-19 vaccines [ 14 , 15 , 18 , 31 , 37 ]. Interestingly, the aforementioned Egyptian study reports higher acceptance among younger HCWs; however, it was not a predictor for COVID-19 vaccination [ 18 ].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations